Proposals for the 2nd Five Year Plan Health Department (Medical) Vol. I Government of Madhya Bharat - Planning Commission (Planning Commission, 1955)
The object of the Scheme is to provide Staff for maintenance of accounts and control over expenditure, implementation of the Flan Schemes expeditiously as well as full utilisation of the amount sanctioned for each Scheme. In the Second Five Year Plan, it is proposed to main provision for the staff already sanctioned under the First Five Year Plan and for the additional posts mentioned.
Government of Madhya Bharat